A participatory surveillance of marsh deer (Blastocerus dichotomus) morbidity and mortality in Argentina: first results - Orozco, María Marcela; Argibay, Hernán Darío; Minatel, Leonardo; Guillemi, Eliana Carolina; Berra, Yanina; Schapira, Andrea; Di Nucci, Dante; Marcos, Andrea; Lois, Fernanda; Falzone, Martín; Farber, Marisa Diana (BMC, 2021)
Background: In an era of unprecedented socio-ecological changes, managing wildlife health demands high-quality data collection and the engagement of local communities. Blastocerus dichotomus, the largest South American deer, is Vulnerable to extinction mainly due to habitat loss. Diseases have been recognised as a potential threat, and winter mortality has been historically described in marsh deer populations from Argentina. Field difficulties have, however, prevented in-depth studies of their health status. Results: Between May 2014 and April 2017, we investigated marsh deer morbidity and mortality in the two largest populations in Argentina. We collected data by means of a passive surveillance system that involved a network of researchers, field partners (veterinarians, park rangers, and local community), and decision makers. We sampled marsh deer during as well as outside mortality events. A total of 44 marsh deer with different body condition scores were evaluated. We obtained haematology and biochemistry values from animals with good body condition score. Marsh deer with poor body condition had a high burden of the ticks Amblyomma triste and Rhipicephalus microplus. Vector-borne agents such as Theileria cervi, Trypanosoma theileri, Trypanosoma evansi, Ehrlichia chaffeensis, Anaplasma platys, Anaplasma odocoilei, Anaplasma marginale, and Candidatus Anaplasma boleense were also found. Haemonchus spp., Ostertagia spp., and Trichostrongylus spp. were the most frequent gastrointestinal parasites in deer with poor body condition. A Multiple Correspondence Analysis reinforced a possible association of winter period with lower body score condition, high tick loads, infection with E. chaffeensis, and presence of harmful gastrointestinal parasites. Conclusions: Our approach allowed the establishment of a participatory surveillance network of marsh deer morbidity and mortality in Argentina. We report and analyse the first data obtained opportunistically within the framework of this network, providing information on the infectious and parasitic agents in marsh deer populations. The occurrence of Fasciola hepatica and Leptospira interrogans serovar pyrogenes is reported for the first time in wild marsh deer from Argentina. Our data will be useful to improve the interpretation of future mortality events. The field implementation of a surveillance network is key to a holistic approach to wildlife diseases.